The Socio-Political Role of Village Kiai in Nahdlatul Ulama Rural Communities: Patron–Client Relations, Symbolic Capital, and the Dynamics of Local Political Fields - Muhammad Sunandar Alwi (Lakpesdam PCNU Kota Salatiga, 2025)
The influence of Nahdlatul Ulama (NU) in rural Indonesia is evident not only in religious practices but also in social relations, the governance of local traditions, and local political dynamics, with kiai kampung serving as nodes of moral authority operating beyond the state’s formal institutional structures. As caretakers of small prayer houses (mushala/langgar) or mosques and as Qur’anic teachers, kiai kampung often become primary references for resolving everyday community problems and act as brokers of legitimacy when social life intersects with contests of interest at the local level. This article addresses three questions: (1) how kiai kampung build and maintain socio-religious legitimacy within NU-affiliated rural communities; (2) how patron–client relations and symbolic capital strengthen the influence of kiai kampung in addressing social problems and governing communal traditions; and (3) how the involvement of kiai kampung in local socio-political arenas reveals an ambivalence between reinforcing social harmony and the risk of co-optation by practical politics. The study employs a conceptual literature review with a critical-theoretical analysis of key scholarship on kiai authority, patron–client relations, and local political-field dynamics. The analytical framework combines charismatic authority to explain sources of informal legitimacy, patron–client theory to examine asymmetric reciprocal exchanges, and the concepts of field and capital to analyse the conversion of religious legitimacy into socio-political influence in local arenas. The argument advanced is that: (1) kiai kampung build and sustain socio-religious legitimacy through charismatic authority reproduced by recurrent socio-religious practices (teaching, communal rituals, and exemplary conduct), which secures their recognition as informal leaders in NU rural settings; (2) their influence in resolving social problems and governing traditions is reinforced by patron–client exchanges that trade moral protection, mediation, and network access for community loyalty and compliance, alongside the accumulation of symbolic capital convertible into social capital; and (3) their engagement in local socio-political fields is ambivalent strengthening social harmony and public ethics through legitimacy brokerage on the one hand, while risking clientelism, polarisation, and the erosion of religious authority when symbolic capital is transformed into political endorsement perceived as transactional on the other. The article recommends strengthening ethical–political literacy and moral accountability through inclusive community deliberation (musyawarah), clarifying boundaries between religious services and political transactions, and conducting further cross-regional ethnographic-comparative studies to map variations in kiai kampung typologies and the mechanisms through which symbolic capital is converted within local politics.